(untitled) (Biological Sciences - PJSIR, 2002)
Ginger Oleoresin exhibited a marked action on central nervous system. The oleoresin was found to be non lethal upto a dose of 3.0g kg·1., while a dose above that resulted in mortalities. The LDSO was found to be 6.284 g kg- 1 . The signs and symptoms observed in non lethal doses were solely functional and short lived. The magnitude and intensities of sign s and symptoms exhibited were found to be dose dependant, while lethal doses im parted pharmacological and toxicological action by affecting the physiological mechanism of the body. Death occurred may be due to the direct action on central nervous system resulting in respiratory failure as well as circulatory arrest.